Cancer Incidence in Physicians: A Taiwan National Population-based Cohort Study. Issue 47 (November 2015) - Lee, Yu-Sung; Hsu, Chien-Chin; Weng, Shih-Feng; Lin, Hung-Jung; Wang, Jhi-Joung; Su, Shih-Bin; Huang, Chien-Cheng; Guo, How-Ran
Abstract : Abstract: Cancer has been the leading cause of death in Taiwan since 1982. Physicians have many health-related risk factors which may contribute to cancer, such as rotating night shift, radiation, poor lifestyle, and higher exposure risk to infection and potential carcinogenic drugs. However, the cancer risk in physicians is not clear. In Taiwan's National Health Insurance Research Database, we identified 14, 889 physicians as the study cohort and randomly selected 29, 778 nonmedical staff patients as the comparison cohort for this national population-based cohort study. Cox proportional-hazard regression was used to compare the cancer risk between physicians and comparisons. Physician subgroups were also analyzed. Physicians had a lower all-cancer risk than did the comparisons (hazard ratio [HR] 0.86, 95% confidence interval [CI] 0.76–0.97). In the sex-based analysis, male physicians had a lower all-cancer risk than did male comparisons (HR 0.82, 95% CI 0.73–0.94); and female physicians did not (HR 1.29, 95% CI 0.88–1.91). In the cancer-type analysis, male physicians had a higher risk of prostate cancer (HR 1.72, 95% CI 1.12–2.65) and female physicians had twice the risk of breast cancer (HR 2.00, 95% CI 1.11–3.62) than did comparisons. Cancer risk was not significantly associated with physician specialties. Physicians in Taiwan had a lower all-cancer risk but higher risks for prostate and breast cancer than did the general population. These new epidemiological findings require additional study to clarify possible mechanisms.